PENERAPAN PENDEKATAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII C PADA MATERI LUAS DAN KELILING LINGKARAN DI MTS BIROBULI - Dewi Sri Wahyuni (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
To improve students' learning outcomes on the broad and circle of the circle, the researcher applied the learning using Contextual Teaching And Learning (CTL) approach. Researchers conduct classroom action research using a qualitative approach. The design of this study refers to the Kemmis and MC models. Taggrt which consists of four components, namely (1) Planning (Planning), (2) Implementation of action (Action), (3) Observation, and (4) reflection. Based on the research result, it was found that the students of grade VIII C MTS Birobuli in cycle I, from 27 students who completed the final test of action there were 13 complete students, so that the percentage of learning completeness equal to 48%, and in cycle II, from 27 students who took the final test action there are 22 complete students with percentage mastery 81%. Based on these results, it can be concluded that the forwarding of learning model Contextual Teaching And Learning (CTL) can improve the learning outcomes of students of class VIII C MTS Birobuli on the circumference material and the area of the circle.